Genome analysis and avirulence gene cloning using a high-density RADseq linkage map of the flax rust fungus, Melampsora lini. (December 2016) - Anderson, Claire; Khan, Muhammad; Catanzariti, Ann-Maree; Jack, Cameron; Nemri, Adnane; Lawrence, Gregory; Upadhyaya, Narayana; Hardham, Adrienne; Ellis, Jeffrey; Dodds, Peter; Jones, David
Abstract Background Rust fungi are an important group of plant pathogens that cause devastating losses in agricultural, silvicultural and natural ecosystems. Plants can be protected from rust disease by resistance genes encoding receptors that trigger a highly effective defence response upon recognition of specific pathogen avirulence proteins. Identifying avirulence genes is crucial for understanding how virulence evolves in the field. Results To facilitate avirulence gene cloning in the flax rust fungus, Melampsora lini, we constructed a high-density genetic linkage map using single nucleotide polymorphisms detected in restriction site-associated DNA sequencing (RADseq) data. The map comprises 13, 412 RADseq markers in 27 linkage groups that together span 5860 cM and contain 2756 recombination bins. The marker sequences were used to anchor 68.9 % of theM. lini genome assembly onto the genetic map. The map and anchored assembly were then used to: 1) show thatM. lini has a high overall meiotic recombination rate, but recombination distribution is uneven and large coldspots exist; 2) show that substantial genome rearrangements have occurred in spontaneous loss-of-avirulence mutants; and 3) identify theAvrL2 andAvrM14 avirulence genes by map-based cloning.AvrM14 is a dual-specificity avirulence gene that encodes a predicted nudix hydrolase.AvrL2 is located in the region of theM. lini genome with the lowest recombination rate and encodes a small, highly-charged proline-rich protein. Conclusions TheM. lini high-density linkage map has greatly advanced our understanding of virulence mechanisms in this pathogen by providing novel insights into genome variability and enabling identification of two new avirulence genes.